W-Band CMOS down-conversion mixer using micromixer-based gain-enhanced technique. Issue 11 (2nd November 2019) - Lin, Yo-Sheng; Lan, Kai-Siang; Peng, Ching-Hung
ABSTRACT: We demonstrate a W-band down-conversion micromixer for imaging and gesture recognition transceiver. Micromixer-based gain-boosted technique, i.e. inductive-peaking gain-boosted single-to- differential transconductance (gm ) stage, is adopted to increase the output impedance and restrain the feedback capacitance Cgd of the gm stage. This leads to the conversion gain (CG), noise figure (NF) and LO-to-RF leakage of the micromixer being significantly improved. The micromixer dissipates 7.2 mW and attains marvellous RF-port return loss of −12.7 −14.7 dB for 85 110 GHz. That is, the −10 dB matching bandwidth is wider than 25 GHz. Moreover, for 90 96 GHz, the micromixer attains CG of 10.5 12 dB and LO-to-RF isolation of 40.2 46.2 dB, one of the highest values ever demonstrated for a W-band mixer/micromixer. The 3 dB CG bandwidth is 22 GHz (83 105 GHz), and the input third-order intercept point (IIP3) is 1 dBm. These results indicate the micromixer is appropriate for W-band imaging and gesture recognition transceivers.